THU0517 Identification of candidate genes associated with fibromyalgia susceptibility in southern spanish women: the al-Ándalus project. (12th June 2018) - Estevez-Lopez, F.; Camiletti-Moirón, D.; Aparicio, V.A.; Segura-Jiménez, V.; Álvarez-Gallardo, I.C.; Soriano-Maldonado, A.; Borges-Cosic, M.; Acosta-Manzano, P.; Geenen, R.; Delgado-Fernández, M.; Martínez-González, L.J.; Ruiz, J.R.; et al.
Abstract : Background: Family aggregation suggests genetic susceptibility to fibromyalgia. 1 Candidate-gene studies on fibromyalgia susceptibility often include a small number of SNPs, 2, 3 which is a limitation. 4 Additionally, there is a paucity of evidence in Europe. Objectives: To compare genotype frequencies of candidate single nucleotide polymorphisms (SNPs) in a well-characterised sample of Spanish women with fibromyalgia and healthy non-fibromyalgia women. Methods: Three hundred and fourteen women with a diagnosis of fibromyalgia (cases) and 112 non-fibromyalgia healthy (controls) women participated in the present candidate-gene study. Buccal swabs were collected for DNA extraction. Using TaqMan OpenArray, we analysed 63 single nucleotide polymorphisms (SNPs) of 33 genes related to fibromyalgia susceptibility, symptoms, or potential mechanisms. Results: The rs841 and rs1799971 GG genotype was more frequently observed in fibromyalgia than in controls (p=0.04 and p=0.02, respectively). The rs2097903 AT/TT genotypes were also more often present in the fibromyalgia participants than in their control peers (p=0.04). Conclusions: We identified, for the first time, associations of the rs841 (guanosine triphosphate cyclohydrolase 1 gene) and rs2097903 (catechol-O-methyltransferase gene) SNPs with higher risk of fibromyalgia susceptibility. We also confirmed that the rs1799971 SNP (opioid receptor μ1 gene) might confer genetic risk of fibromyalgia. Further studies are needed to confirm or refute the present findings. References: [1] Arnold LM, et al. Arthritis Rheum2004;50(3):944–52. [2] Lee YH, et al. Rheumatol Int2012;32(2):417–26. [3] Estévez-López F, et al. Rheumatol Int (in press). doi:10.1007/s00296-017-3896-x [4] Klepstad P. Scand J Pain2014;5:8–9. Acknowledgements: The authors report no conflicts of interest. This work was supported by the Spanish Ministry of Economy and Competitiveness [I+D+ i DEP2010–15639, I+D+ i DEP2013–40908 R, BES-2014–0 67 612]; the Spanish Ministry of Education [FPU2014/02518] Disclosure of Interest: None declared